"Aeneid" by I.Kotliarevskyi as a fanfiction work (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article is devoted to research of fanfiction as a kind of modern literary works, literary anomaly. Indicated that works of fanfiction are independent texts but they have a derivative character. An attempt to understand the «Аеneid» by Kotlyarevskyi as one of the first works of fanfiction in Ukrainian literature is made.
Keywords: fanfiction; canon; literary anomaly; interpretation; «recognition code»